To solve the equation \( 37x + 67 - 2x = 4 \), we can start by simplifying the left-hand side.
-
Combine like terms: \[ 37x - 2x + 67 = 4 \] This simplifies to: \[ 35x + 67 = 4 \]
-
Next, subtract 67 from both sides: \[ 35x = 4 - 67 \] \[ 35x = -63 \]
-
Now, divide both sides by 35: \[ x = \frac{-63}{35} \]
-
Simplify the fraction: \[ x = \frac{-63 \div 7}{35 \div 7} = \frac{-9}{5} \]
The value \( x = -\frac{9}{5} \) does not match any options you've given. However, you might want to check your options because based on what is provided, none correspond to \( -\frac{9}{5} \).
If you have further details or would like to double-check the equation, please share!